Analisis Minat Pembelian Produk Preloved Sebagai Upaya Peduli Lingkungan - Yuliana, Lingga; Apriyana, Nurliya; Fauzan, Ray; Larasati, Nike; Alhazami, Lutfi; Eko Bima Sutopo, Israel (Catholic University Musi Charitas, 2023)
This research aims to investigate purchasing interests in preloved products from reputable brands as an environmental care effort. The advantage of conducting this study is to provide a resource for readers and researchers considering similar issues. In this descriptive qualitative research, purposive sampling was used to select the samples. The samples that met the criteria of this study were those who had previously bought the branded product from offline or online shops. Ten respondents were involved in the survey of this study. The questionnaires were distributed via Google form and conducted from November 2022 to January 2023. The findings reveal purchasing pre-owned branded goods contributes to environmental protection by minimizing unrecycled fashion trash and animal exploitation. The respondents recommended purchasing pre-owned branded goods responsibly to protect the environment and get products at reasonable rates.